Nasionalisme dan Perjalanan Demokrasi - Asnawi Umar Ali (Unisia, 2005)
In Indonesia the nationalism discourse has been placed on the debate between Tjipto Mangoen Koesoemo and Soetatmo Soerjokoesoemo. Tjipto established the Budi Utomo and the Indische Partij, meanwhile Soetomo founded the Javanese Nationalism Comiittee. In 1918 the debate was published as flyers entitle "Javanese of indische Nationalism." Soetatmo made the Javanese nationalism more in progress based on the language and culture for the national interest. On this perspective, Soetatmo proposed the role of the pandito as the creator of peace on the chaos movement by improving the relationship between people and princes; In this regard the people became the ordinary people devoting to the lord. On the other side, Tjipto stood with his Indische nationalism due to the reincarnation of the true noble with its glorious morality, through the resistance with no compromise for the oppression and exploitation conducted by the Dutch and the upper class (priyayi) to the ordinary people.